2018
DOI: 10.1182/blood-2017-07-798306
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasma clot properties increase the risk of recurrent deep vein thrombosis: a cohort study

Abstract: It has been demonstrated that fibrin clots generated from plasma samples obtained from patients with prior thromboembolic events are denser and less susceptible to lysis. Such a prothrombotic fibrin clot phenotype has been suggested as a new risk factor for venous thromboembolism, but its prognostic value is unclear. To assess whether abnormal clot properties can predict recurrent deep vein thrombosis (DVT), we studied 320 consecutive patients aged 18 to 70 years following the first-ever DVT. Plasma clot prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 41 publications
8
81
0
1
Order By: Relevance
“…In our study patients diagnosed with malignancy were older, and advanced age is reported to be associated with prothrombotic fibrin clot properties . We observed longer CLT in men; however, the impact of sex on fibrin properties is uncertain . In our previous study we did not observe differences in fibrin clot properties between men and women .…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…In our study patients diagnosed with malignancy were older, and advanced age is reported to be associated with prothrombotic fibrin clot properties . We observed longer CLT in men; however, the impact of sex on fibrin properties is uncertain . In our previous study we did not observe differences in fibrin clot properties between men and women .…”
Section: Discussionsupporting
confidence: 39%
“…The so‐called prothrombotic clot phenotype,that is, a combination of increased density of fibrin clot networks, reflected by low permeability coefficient (K s ) and reduced overall efficiency of fibrinolysis (CLT), has been demonstrated to predispose to VTE and its recurrences . Similar prothrombotic clot characteristics have been found in patients with gastrointestinal cancers and lung cancer…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, previous work has shown that clot structures for samples from patients with recurrent and nonrecurrent PE were different, with recurrent PE clots being more densely packed and less porous than non-recurrent PE clots, although these clots were made with purified fibrinogen [24]. Similarly, it was shown that recurrent DVT was associated with less permeable clots than non-recurrent DVT, suggesting that these clots are less porous [25]. In the current study, turbidity experiments showed that there was a higher maximum absorbance for nrVTE plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Moreover, following discontinuation of anticoagulation after first DVT, faster formation of less permeable fibrin networks and prolonged clot lysis time is associated with increased risk of DVT recurrence (odds ratio 15.8; confidence interval 7.5–33.5). (21) Abnormal clot properties, including reduced plasma clot permeability and susceptibility to fibrinolysis are also associated with increased risk of developing long-term sequelae, including chronic thromboembolic pulmonary hypertension, post-thrombotic syndrome, and persistent venous obstruction. (2224) Notably, although these observations are of platelet-poor plasma clots formed ex vivo, their association with VTE risk suggests these clot properties recapitulate aspects of venous thrombus (dys)function in vivo.…”
Section: Fibrin Formation Structure and Function In Vtmentioning
confidence: 99%